2022
DOI: 10.1177/20499361221095679
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, healthcare resource utilization, and cost among Medicare beneficiaries with Clostridioides difficile infection with and without sepsis

Abstract: Objective: To describe mortality, healthcare resource utilization (HRU), and costs among Medicare beneficiaries with primary Clostridioides difficile infection (pCDI) or recurrent CDI (rCDI), with and without sepsis. Methods: We conducted a retrospective observational study of 100% Medicare Fee-for-Service claims from adults aged ⩾ 65 years with ⩾1 CDI episode between 1 January 2009 and 31 December 2017. Patients were continuously enrolled in Medicare Parts A/B/D 12 months before and up to 12 months after pCDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…CDI is a serious illness that can lead to complications, including sepsis, colectomy, and death – the risks of which increase with each subsequent CDI recurrence. 18,36 Recent retrospective claims analyses found that approximately 27% of patients aged 18–64 years and 35% of patients aged ⩾65 years with one rCDI event experienced sepsis within 12 months of the initial CDI; these percentages are 20–30 times greater than the less than 1% of participants treated with RBL that experienced sepsis or bacteremia. 18,37 Importantly, there were no reported infections for which the causative pathogen was traced to RBL.…”
Section: Discussionmentioning
confidence: 99%
“…CDI is a serious illness that can lead to complications, including sepsis, colectomy, and death – the risks of which increase with each subsequent CDI recurrence. 18,36 Recent retrospective claims analyses found that approximately 27% of patients aged 18–64 years and 35% of patients aged ⩾65 years with one rCDI event experienced sepsis within 12 months of the initial CDI; these percentages are 20–30 times greater than the less than 1% of participants treated with RBL that experienced sepsis or bacteremia. 18,37 Importantly, there were no reported infections for which the causative pathogen was traced to RBL.…”
Section: Discussionmentioning
confidence: 99%
“…Despite current antibiotic treatments, patients with rCDI experience a disproportionately higher economic burden due to elevated use of healthcare resources, including increased hospitalization and post-acute care, and more costly surgeries compared to patients with CDI who have not experienced a recurrence, ICER results are subject to rounding errors. Precise values of costs and effectiveness with more decimals were used in the model calculation FMBL fecal microbiota, live-jslm, ICER incremental costeffectiveness ratio, LY life year, QALY quality-adjusted life year, SOC standard of care, USD United States dollar let alone a higher mortality [23,33,34]. FMBL is the first in class microbiota-based live biotherapeutic which demonstrated efficacy in the prevention of rCDI following antibiotic treatment in clinical trials [6].…”
Section: Discussionmentioning
confidence: 99%
“…Significant health complications of CDI include sepsis, colectomy, megacolon, intestinal perforation, and renal failure [ 42 ]. An analysis of three different sources, a commercial younger CDI related population, Medicare and all-cause data from the United Kingdom shows the incidence of complications and surgical intervention increases with rCDI, all of which contribute to longer hospital stays, ICU requirements, and high inpatient admission rates [ 38 , 42 , 55 ].…”
Section: The Likelihood Of Complications Is High With CDI and Rcdimentioning
confidence: 99%
“…2 ) [ 38 ]. Rates are higher for older patients with 39% of Medicare patients with CDI suffering sepsis, increasing to 45% in those with rCDI [ 55 ]. Mortality associated with sepsis is very high with in-hospital, 30-day, and 12-month mortality rates of 24% [ 60 ], 30% [ 61 ], and 58% [ 55 ], respectively.…”
Section: The Likelihood Of Complications Is High With CDI and Rcdimentioning
confidence: 99%
See 1 more Smart Citation